Pelatihan Model Pembelajaran Berbasis Inductive Thinking Bagi Guru-Guru Sekolah Dasar - Risal M. Merentek; Steven Mandey (Peneliti.net, 2021)
Learning is a process of effort carried out by a person to obtain a new behavior change as a whole, as a result of his own experience in interaction with the environment. The teaching process in the classroom is an interaction between teachers and students. Interaction in the classroom can be carried out properly if students understand the material presented by the teacher. The inductive thinking learning model includes a learning model that is included in the information processing model, where students provide responses that come from their environment by organizing data, formulating problems, building concepts and problem-solving plans and using verbal and non-verbal symbols. This model provides students with a number of concepts, tests hypotheses, and focuses on developing creative abilities. In this activity, the implementation method is carried out in the form of: training, workshops and mentoring. The method used in training, workshops and mentoring is in the form of a cycle which is carried out in five stages, namely: the planning stage, the action stage, the observation stage, the reflection stage, and the follow-up stage. Training activities and the development of new learning models for teachers will certainly build teachers' mindsets on how important it is to design learning, apply learning theory and determine learning strategies, mastery of scientific material, mastery of school curriculum and syllabus, special methods of learning in the field of study, and insight into ethics and professional development